Itolizumab as the First Line of Treatment in Moderate to Severe Chronic Plaque Psoriasis- A Case Report - Trasi, Shrilata S.; Sashidharan, Nithin (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Psoriasis is a chronic, autoimmune disease with a genetic predisposition. Among the various therapeutic options, biological therapies are emerging as a novel therapy in the management of this disease. Here, we present a case report of a patient who received Itolizumab as the first line of therapy. Keywords: Psoriasis, Biologic, Itolizumab